2022
DOI: 10.17350/hjse19030000262
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Economic Analysis of Energy Recovery from Municipal Solid Waste in Yola Metropolis, Adamawa State, Nigeria

Abstract: There has been an increase in the general spending and consumption habit of people, the consequence of which is an increase in the quantity of municipal solid wastes (MSW) being generated particularly in urban areas. Yola, the capital of Adamawa State in the northeast region of Nigeria an urban area also has its share of problems associated with solid wastes management. In addition, the city like most other cities in Nigeria experiences inadequate electricity supply. Hence the need for this research - to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Their findings revealed that the residual waste in Abuja and Lagos cities can generate 54 GWh/year and 475 GWh/year respectively. [20] investigated the energy generation potential and economic viability of organic MSW in the 21 LGAs of Anambra State of Nigeria. They found that a large-scale plant of about 50 m 3 can possibly be installed at all the LGAs including Onitsha North.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings revealed that the residual waste in Abuja and Lagos cities can generate 54 GWh/year and 475 GWh/year respectively. [20] investigated the energy generation potential and economic viability of organic MSW in the 21 LGAs of Anambra State of Nigeria. They found that a large-scale plant of about 50 m 3 can possibly be installed at all the LGAs including Onitsha North.…”
Section: Introductionmentioning
confidence: 99%
“…They found that a large-scale plant of about 50 m 3 can possibly be installed at all the LGAs including Onitsha North. [21] conducted an assessment of the technical and economic potentials of recovering energy from the MSW generated in Yola metropolis of Nigeria based on the incineration technology method. Their findings revealed that the average calorific value of the MSW disposed of in the city's dumpsite is 1515.67 kcal/kg, with the potential to produce a total of 3,748.60 kW of electrical energy from the three dumpsites studied.…”
Section: Introductionmentioning
confidence: 99%